Alpha lipoic acid attenuates ER stress and improves glucose uptake through DNAJB3 cochaperone - Abdoulaye Diane (14152749) (2020)
Persistent ER stress, mitochondrial dysfunction and failure of the heat shock response (HSR) are fundamental hallmarks of insulin resistance (IR); one of the early core metabolic aberrations that leads to type 2 diabetes (T2D). The antioxidant α-lipoic acid (ALA) has been shown to attenuate metabolic stress and improve insulin sensitivity in part through activation of the heat shock response (HSR). However, these studies have been focused on a subset of heat shock proteins (HSPs). In the current investigation, we assessed whether ALA has an effect on modulating the expression of DNAJB3/HSP40 cochaperone; a potential therapeutic target with a novel role in mitigating metabolic stress and promoting insulin signaling. Treatment of C2C12 cells with 0.3 mM of ALA triggers a significant increase in the expression of DNAJB3 mRNA and protein. A similar increase in DNAJB3 mRNA was also observed in HepG2 cells. We next investigated the significance of such activation on endoplasmic reticulum (ER) stress and glucose uptake. ALA pre-treatment significantly reduced the expression of ER stress markers namely, GRP78, XBP1, sXBP1 and ATF4 in response to tunicamycin. In functional assays, ALA treatment abrogated significantly the tunicamycin-mediated transcriptional activation of ATF6 while it enhanced the insulin-stimulated glucose uptake and Glut4 translocation. Silencing the expression of DNAJB3 but not HSP72 abolished the protective effect of ALA on tunicamycin-induced ER stress, suggesting thus that DNAJB3 is a key mediator of ALA-alleviated tunicamycin-induced ER stress. Furthermore, the effect of ALA on insulin-stimulated glucose uptake is significantly reduced in C2C12 and HepG2 cells transfected with DNAJB3 siRNA. In summary, our results are supportive of an essential role of DNAJB3 as a molecular target through which ALA alleviates ER stress and improves glucose uptake. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-77621-x